Extracraniofacial anomalies in Treacher Collins syndrome: A multicentre study of 248 patients. Issue 11 (November 2021) - Beaumont, C.A.; Dunaway, D.J.; Padwa, B.L.; Forrest, C.; Koudstaal, M.J.; Caron, C.J.J.M.
Abstract: Treacher Collins syndrome (TCS) is a congenital malformation of the craniofacial structures derived from the first and second pharyngeal arches. The craniofacial deformities are well described in the literature. However, little is known about whether there are associated extracraniofacial anomalies. A retrospective study was conducted using data from four craniofacial units. Medical charts were reviewed for the presence and type of extracraniofacial anomalies, as well as age at diagnosis. A possible correlation between the severity of the phenotype and the presence of extracraniofacial anomalies was assessed using the Hayashi classification. A total of 248 patients with TCS were identified; 240 were confirmed to have TCS, of whom 61 (25.4%) were diagnosed with one or more extracraniofacial anomalies. Ninety-five different extracraniofacial anomalies were found; vertebral ( n  = 32) and cardiac ( n  = 13) anomalies were most frequently seen, followed by reproductive system ( n  = 11), central nervous system ( n  = 7), and limb ( n  = 7) anomalies. No correlations between tracts were found. Extracraniofacial anomalies were more prevalent in these patients with TCS compared to the general population (25.4% vs 0.001–2%, respectively). Furthermore, a positive trend was seen between the severity of the syndrome and the presence of extracraniofacial anomalies. A full clinical examination should be performed on any new TCS patient to detect any extracraniofacial anomalies on first encounter with the craniofacial team.